2019
DOI: 10.1021/acsmacrolett.9b00169
|View full text |Cite
|
Sign up to set email alerts
|

Cation-Directed Self-Assembly of Macrocyclic Diacetylene for Developing Chromogenic Polydiacetylene

Abstract: The cation-directed self-assembly process has emerged as a fascinating approach for constructing supramolecular architectures and manifested a diverse range of assembly related applications. Herein, we synthesized a macrocyclic structure containing bis-amidopyridine and photopolymerizable diacetylene template, PyMCDA. Owing to the metal coordination affinity of bis-amidopyridine and the π−π stacking characteristic of diacetylene template and complementary to the cyclic molecular framework, Cs + -directed organ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
35
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(36 citation statements)
references
References 35 publications
1
35
0
Order By: Relevance
“…[17,18] Tremendouse fforts have been made towards aligning diacetylene molecules into hierarchical nanostructurest hrough various techniques involvingn on-covalent forces. [19][20][21] Nevertheless, limited successh as been achieved, presumably owing to the strict packingr equirements of topochemical polymerization and the numerous defects that may evolve during the preparation and polymerization processes. [22] Ab etter understanding and improvedc ontrol of the self-assembling behaviors for diacetylene molecules are needed.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[17,18] Tremendouse fforts have been made towards aligning diacetylene molecules into hierarchical nanostructurest hrough various techniques involvingn on-covalent forces. [19][20][21] Nevertheless, limited successh as been achieved, presumably owing to the strict packingr equirements of topochemical polymerization and the numerous defects that may evolve during the preparation and polymerization processes. [22] Ab etter understanding and improvedc ontrol of the self-assembling behaviors for diacetylene molecules are needed.…”
Section: Introductionmentioning
confidence: 99%
“…Pre‐organizing diacetylenic monomers directionally and then subjecting them to topochemical polymerization to form aligned conjugated polymers are highly interesting [17, 18] . Tremendous efforts have been made towards aligning diacetylene molecules into hierarchical nanostructures through various techniques involving non‐covalent forces [19–21] . Nevertheless, limited success has been achieved, presumably owing to the strict packing requirements of topochemical polymerization and the numerous defects that may evolve during the preparation and polymerization processes [22] .…”
Section: Introductionmentioning
confidence: 99%
“…Cyclic monomers containing multiple diacetylene units (macrocyclic diacetylenes, MCDA) are established as excellent precursors for the topochemical synthesis of PDA-based organic tubular polymers that possess nanometre-sized interior cavities. 2 d ,27 Suitably functionalized MCDAs containing multiple DA units self-stack into a columnar assembly through non-covalent interactions, 28 sometimes aided by templates, 29 forming a supramolecular nanotube. The subsequent 1,4-addition polymerization of the DA units along the columns results in nanotubular polymers, bearing PDA side-walls.…”
Section: Tubular Polymersmentioning
confidence: 99%
“…Interestingly, self-assemblies of macrocycles containing diacetylene moieties should have columnar structures, which upon polymerization would generate PDAs having rigid, carbon nanotube (CNT)-like structures. [16][17][18][19][20][21][22][23] In an effort to further explore this fascinating feature of PDAs, we designed and synthesized several functional macrocyclic diacetylenes (MCDAs) and demonstrated that they undergo columnar packing and UV-induced polymerization to produce tubular PDAs. [20][21][22][23] Thus far, studies carried out in this area have only focused on PDA nanotubes that are generated from assemblies of single MCDA components.…”
Section: Introductionmentioning
confidence: 99%